Role of the St. Petersburg Paradox in Decision-Making - Samuilovich Gasparian, Mikhail; Anatolievna Kiseleva, Irina; Gennadievich Korneev, Dmitry; Arkadyevich Lebedev, Sergey; Arkadyevich Lebedev, Viktor (International Journal of Engineering and Technology, 2018)
The article considers the appearance and modern interpretations of the St. Petersburg paradox. A review of the main solutions of the St. Petersburg paradox and an attempt to define their significance for the economic theory have been made. The impact of this problem on the economic theory can be seen by the example of such provisions as the principle of diminishing marginal utility, the use of expected utility as a criterion for decision-making in the context of uncertainty, as well as the basics of microeconomics of insurance and risk management, game theory, and some approaches to financial modeling. Â